Implementation of Bridge Filtering to Prevent DHCP Starvation Attack (Case Study: SD Inpres Papindung) - Yosua Nggaba Patimay; Fajar Hariadi; Raynesta Mikaela Indri Malo (Yayasan Kita Menulis, 2025)
The impact of internet cut off or disrupted at SD Inpres Papindung, the teachers will have difficulty finding teaching materials and may have to return to traditional methods that are less effective. Updating Dapodik data will also be disrupted, which could affect school administration and evaluation. The unavailability of an internet connection does occur due to technical reasons or due to intentional elements, one of which is the use of Yersinia software. Yersinia is a piece of software that is commonly used to attack available networks by sending fake MAC addresses continuously so that the IP address on the DHCP server runs out, so that the client does not get an IP address which causes the client unable to access the internet. This attack are called DHCP Starvation Attack. This can be prevented using Bridge Filtering method. Bridge Filtering can filter only recognized MAC addresses to transmit data or can request an IP address from the DHCP server, while MAC addresses that are not recognized or foreign devices will not be allowed to request from that port or will not receive an IP address from the DHCP server. The aim of implementing Bridge Filtering is to measure the creativity of the Bridge Filtering method in preventing DHCP Starvation Attack attacks so that clients who want to connect to the network can access the internet and improve network quality at SD Inpres Papindung.The results show that the Bridge Filtering method effective in preventing DHCP Starvation Attacks and improves network quality at SD Inpres Papindung which is shown by an increase of throughput, before implementation it was 794.66 Kbps and after implementation it was 1283.70 Kbps, there was a decrease of delay from 6.89 ms before implementation to 4.06 ms after implementation. There was also a decrease in jitter before implementation 10.56 ms and after implementation 6.05 ms, but caused an increase in packet loss which was 0.30% before implementation and after implementation increased to 0.79%. Of the four variables, all of them remain at the same level except for the throughput variable, where there is a change from the fair category to the good category, so that it has an impact on the quality of the internet network at SD Inpres Papindung after implementing Bridge Filtering which is stated to be better than before implementing Bridge Filtering on the internet network at SD Inpres Papindung.